2013
DOI: 10.1186/1471-2393-13-81
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the use of prenatal care by non-western women in industrialized western countries: a systematic review

Abstract: BackgroundDespite the potential of prenatal care for addressing many pregnancy complications and concurrent health problems, non-western women in industrialized western countries more often make inadequate use of prenatal care than women from the majority population do. This study aimed to give a systematic review of factors affecting non-western women’s use of prenatal care (both medical care and prenatal classes) in industrialized western countries.MethodsEleven databases (PubMed, Embase, PsycINFO, Cochrane,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 30 publications
6
87
0
4
Order By: Relevance
“…The effect was more significant among women with at least secondary school education. The data is consistent with studies from Ghana (Arthur, 2012), migrants in Western (Boerleider, et al, 2013), Brazil (Coimbra et al, 2007), Nigeria (Iyaniwura and Yussuf, 2009), Nepal (Joshi et al, 2014), Ethiopia (Tekelab and Berhanu, 2014). Thus, improving the education of mothers will contribute greatly to the use of maternal and prenatal services by women and thus help in reducing maternal and child mortality.…”
Section: Discussionsupporting
confidence: 77%
“…The effect was more significant among women with at least secondary school education. The data is consistent with studies from Ghana (Arthur, 2012), migrants in Western (Boerleider, et al, 2013), Brazil (Coimbra et al, 2007), Nigeria (Iyaniwura and Yussuf, 2009), Nepal (Joshi et al, 2014), Ethiopia (Tekelab and Berhanu, 2014). Thus, improving the education of mothers will contribute greatly to the use of maternal and prenatal services by women and thus help in reducing maternal and child mortality.…”
Section: Discussionsupporting
confidence: 77%
“…Innovative community programmes addressing refugee maternal and child health inequalities 68 and antenatal care programmes associated with partnerships between midwives and Aboriginal health workers are underway in Australia. 69,70 Universally, women whose first language differs from the dominant national languages should be offered care and information in their own language, 71 with a choice of the gender of the interpreter. 68 The US Affordable Care Act 72 will provide services such as free contraception, screening for infections, and programmes for alcohol and smoking cessation.…”
Section: Beyond Health-care Deliverymentioning
confidence: 99%
“…A UK study 27 examined the effect of caseload midwifery practices on a culturally diverse group and one Australian study 4 compared the obstetric intervention rates and birth outcomes between Australian and overseas born. Also included in the review were ten literature reviews 6,7,[27][28][29][30][31][32][33][34] (Table 3), one book chapter, 22 and three scholarly, but non-research articles; a clinical paper on the Migrant Health Guide in UK, 35 a report from the Lancet 36 and To explore the links between multiple deprivations and use of maternal services 21 Singh an opinion piece in Australian Midwifery News by an Indian midwife. 37 No research article was found specifically exploring Indian women's childbearing experiences in Australia.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…24 Migrant women noted that when their care provider showed interest and respect, this alleviated their anxiety about coming into a health facility in a new country. 33 Many Indian women in labour valued being cared for by known midwives, 38 and during the postnatal period they valued being supported by family members. 23 While it is beneficial for any pregnant woman to be able to build a trusting relationship and good communications with her carer, it is especially important for those from a culturally diverse background.…”
Section: Discussionmentioning
confidence: 99%